Studies on use of sodium poly acrylate (SPA) for low salt animal skinpreservation - Sandhya, K. V.; Brindha, Velappan; Abinandan, Sudharsanam; Vedaraman, N.; John, Sundar V.; Suresha, P. R.; Badiger, Manohar; Chinnaraj, Velappan kandukalpatti; Muralidharan, C. (IULTCS CONGRESS 2017, 2017)
In this study, commercial sodium poly acrylate (SPA) is used along with sodium chloride for low salt skin preservation. SPA is a super-absorbent polymer which can absorb water many times of its own weight.

One-pot synthesis of bimodal (macro-meso, micro-mesoporous) silica by polyHIPE: parameter studies - Wale, Apparav; Nalawade, Archana; Ponrathnam, Surendra; Rajan, C. R.; Badiger, Manohar (Journal of Porous Materials, 2020)
Porous silica with hierarchical organization of pore structure is desired for a variety of applications such as, chromatography, sensing, control release, scaffold for biomedical applications and catalysis. Highly porous polymers obtained from high internal phase emulsion (HIPE) templating route have attracted increasing attention of researchers due to their hierarchical porous and interconnected structure with high porosity and low density. The novel method adopted in our approach combines redox initiated polymerization using HIPE polymerization and an in-situ sol-gel processing technique followed by calcination to obtain highly porous materials. The obtained materials have reminiscent of polyHIPE morphology containing pores and interconnected pore throats in micrometer size range with mesopores on the wall of macropores. The effect of concentration of TEOS, volume of dispersed phase, crosslinker concentration, shear rate and surfactant concentration as well as variation in calcination temperatures on the properties of silica materials were examined.
Keywords: Mesoporous material; PolyHIPE; Polymer-silica hybrid; Porous silica

Mechanical and microstructural studies in a polysaccharide-acrylate double network hydrogel - Torris, Arun; Nair, Sanoop; Mol, K. P. Raji; Sengupta, Poulomi; Badiger, Manohar (Journal of the Mechanical Behavior of Biomedical Materials, 2021)
Polymeric hydrogels continue to find a wide range of applications. However, a major drawback of hydrogels is the lack of mechanical strength. In this regard, ``Double Network Hydrogels'' (DN) have shown great promise recently. The toughness in DN hydrogels originates from the synergistic effect of two polymeric networks. In this work, we have synthesized a DN hydrogel consisting of a tightly cross linked carboxymethylcellulose (CMC) as the first network and loosely cross linked poly(hydroxyethylacrylate) (PHEA) as a second network (CMC-PHEADN). The required flexibility in the second network (PHEA) was induced by the presence of a small amount of stearyl methacrylate (SM) as a co-monomer in hydroxyl ethyl acrylate (HEA). The compressive strength of the CMC-PEHA-DN hydrogel was found to be 280 times more than that of CMC-SN hydrogel, and the presence of SM in DN hydrogels showed better recovery after deformation. Cell viability studies showed the biocompatibility of DN hydrogels. The micro-structural analysis of DN xerogels by 3D X-ray Microtomography indicated the presence of oriented pores in size range of 30-40 mu m. To the best of our knowledge, Microtomography was used for the first time to study the DN gels. These hydrogels can be used to develop implants that can withstand prolonged stress and expand the life span of implants.
Keywords: Carboxymethyl cellulose; Double network hydrogels; Poly(hydroxyethyl acrylate); Poly(hydroxyethyl-co-stearyl methacrylate)

Silver nanoparticles in electrospun ethyl hydroxy ethyl cellulose-PVA Nanofiber: synthesis, characterization and wound dressing applications - Wali, Ashwini; Gorain, Mahadeo; Kundu, Gopal; Badiger, Manohar (Carbohydrate Polymer Technologies and Applications, 2024)
<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Electrospinning is a simple, cost-effective technique and a reproducible process for both synthetic and <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/natural-polymer" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about natural polymers from ScienceDirect's AI-generated Topic Pages">natural polymers. It is found to be an attractive tool for various applications in biomedical engineering, filtration, protective clothing, catalysis reactions and sensors. Non-ionic cellulose ethers namely Ethyl Hydroxy <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/ethyl-cellulose" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about Ethyl Cellulose from ScienceDirect's AI-generated Topic Pages">Ethyl Cellulose (EHEC) is an important <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/polysaccharide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about polysaccharide from ScienceDirect's AI-generated Topic Pages">polysaccharide which is non-toxic, biocompatible and biodegradable and finds applications as thickening/rheology control agents in paints, cosmetics, detergents, oil recovery and also in the biomedical area. Poly (vinyl alcohol) (PVA) is a semi-crystalline <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/hydrophilic-polymers" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about hydrophilic polymer from ScienceDirect's AI-generated Topic Pages">hydrophilic polymer which is highly biocompatible and non-toxic having good thermal and mechanical properties and also high water solubility. Silver shows powerful antimicrobial activity and is non-toxic. It has been used to cure severe burns and chronic ulcers for many decades and is extensively used as an additive in various fields like prostheses, burn treatment, catheters, vascular grafts, dental resin components, ion exchange fibers, <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/stainless-steel" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about stainless steel from ScienceDirect's AI-generated Topic Pages">stainless steel materials, human skin and coating of <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/medical-device" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about medical devices from ScienceDirect's AI-generated Topic Pages">medical devices. In the present work, EHEC/PVA <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers embedded with silver <a class="topic-link" href="https://www.sciencedirect.com/topics/chemical-engineering/nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanoparticles from ScienceDirect's AI-generated Topic Pages">nanoparticles (AgNPs) are studied for their <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/antibacterial-activity" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about antibacterial activity from ScienceDirect's AI-generated Topic Pages">antibacterial activity using both gram positive and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/gram-negative-bacterium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about gram negative bacteria from ScienceDirect's AI-generated Topic Pages">gram negative bacteria. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers show increase in <a class="topic-link" href="https://www.sciencedirect.com/topics/materials-science/tensile-property" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about tensile properties from ScienceDirect's AI-generated Topic Pages">tensile properties with the addition of silver nano-particles. The <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/silver-nanoparticle" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about AgNPs from ScienceDirect's AI-generated Topic Pages">AgNPs embedded EHEC/PVA nanofiber mats having 0.5% AgNPs were found to enhance the <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound-healing" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wound healing from ScienceDirect's AI-generated Topic Pages">wound healing with no scar formation in <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wistar-rat" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wistar rats from ScienceDirect's AI-generated Topic Pages">wistar rats. The biological <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vitro<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> and <em style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">in-vivo<span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> studies support the potential of EHEC based <a class="topic-link" href="https://www.sciencedirect.com/topics/agricultural-and-biological-sciences/nanofiber" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about nanofibers from ScienceDirect's AI-generated Topic Pages">nanofibers as excellent bio-materials for the treatment of severe burns and <a class="topic-link" href="https://www.sciencedirect.com/topics/pharmacology-toxicology-and-pharmaceutical-science/wound" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: rgba(0, 0, 0, 0); word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(31, 31, 31); color: rgb(31, 31, 31); text-underline-offset: 1px;" title="Learn more about wounds from ScienceDirect's AI-generated Topic Pages">wounds. To the best of our knowledge, this is the first report on the electrospinning of EHEC/PVA nanofibers for wound healing applications.

Microgels of hydrophobically modified-ethyl hydroxy ethyl cellulose (HM-EHEC) with 5-flurouracil for drug delivery applications - Wali, Ashwini; Badiger, Manohar (Research Journal of Biotechnology, 2025)
The polysaccharides (e.g. celluloses and proteins) which form the basic building blocks of life, are gaining increased interest in recent times for researchers to develop newer health care products from renewable bio-polymers which are cheaper and easily available with different desirable properties. Gels are highly swollen three dimensional networks of hydrophilic polymers cross-linked by physical or chemical interactions. Our focus was to design and develop a novel microgel system which would effectively deliver the anti-cancer drug to the targeted site by slow and sustained release for longer times. The water soluble hydrophobically modified ethyl hydroxy ethyl cellulose (HM-EHEC) biopolymer was used in the synthesis of microgels by Michael-type addition reaction between the primary hydroxyl groups of HM-EHEC and Divinyl sulphone (DVS) crosslinker using water-in-oil emulsion technique. The microgels obtained were spherical in shape having flower type morphology with average size of 5 to 8 μm. The anti-cancer drug 5-Flurouracil (5-FU) drug was successfully incorporated and around 56% of the 5-FU was released in 72 hours with a loading efficiency of 95%. The cell viability (MTT assay) studies confirmed the cycto-toxicity on the MDA-MB 231 breast cancer cell line. There was an increase in the cell death with increase in the concentration of microgel containing drug concentration. The HM-EHEC microgels could be effectively used in the form of a topical cream in the skin and breast cancer for on-site slow and targeted delivery.